2012
DOI: 10.1097/nnr.0b013e31825fe3ef
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Rural Village Women (Asha) Intervention on Adherence to Antiretroviral Therapy in Southern India

Abstract: Background Despite the increased prevalence of HIV in the rural female population of India, adherence to antiretroviral therapy continues to be low due to several barriers which discourage rural women. Objectives To assess the effectiveness of an intervention (Asha-Life) delivered by Accredited Social Health Activists to improve antiretroviral therapy adherence of rural women living with AIDS in India compared to that of a usual care group. Method A total of 68 rural women living with AIDS, aged 18–45 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 30 publications
2
38
1
1
Order By: Relevance
“…The impact of the program on the physical health of WLA was also reported by the women in terms of CD4 counts and body weight and concur with other research studies (Nyamathi, Hanson, et al, 2012; Nyamathi, Salem, Ernst, Keenan, Suresh, Sinha, Ganguly, Ramakrishnan, & Liu, 2012). …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The impact of the program on the physical health of WLA was also reported by the women in terms of CD4 counts and body weight and concur with other research studies (Nyamathi, Hanson, et al, 2012; Nyamathi, Salem, Ernst, Keenan, Suresh, Sinha, Ganguly, Ramakrishnan, & Liu, 2012). …”
Section: Discussionsupporting
confidence: 90%
“…At six month follow up, the researchers revealed that adherence to ART, CD4 levels, and depressed mood were significantly improved with the AL group as compared to the UC program (p < .001) (Nyamathi, Hanson, et al, 2012; Nyamathi, Salem, Meyer et al, 2012). The AL participants also had significantly greater odds of reducing depressive mood than the UC group (Nyamathi, Salem, Meyer et al, 2012).…”
Section: Asha-life and Usual Care Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative studies, reviews or editorials, research published in abstract form only or that did not undergo peer review, studies examining adherence to preor post-exposure prophylaxis or prophylaxis for the prevention of mother-to-child transmission, and any studies that did not report a measure of association between food insecurity or food assistance and adherence were excluded. Methods for the review and inclusion criteria were specified in advance, with the following additional inclusion criteria specified after the full text review: (1) definition of treatment interruption as non-adherence for at least 3 months and exclusion of papers examining treatment interruption as the outcome, (2) exclusion of two papers identified in the search that compared adherence in two groups of wasted HIV patients receiving different types of food supplements [28,29]; and (3) exclusion of studies identified in the search that evaluated combination support programs for PLHIV that included a nutritional component but did not present or permit estimation of the individual effect of food assistance distinct from the other services in the program [30][31][32][33]. Although we did not limit inclusion to adult populations, no studies examined the association between food insecurity and ART adherence in pediatric populations, and only one study examined the association between food assistance and adherence in a pediatric population [34], but was excluded because it did not specify the type of food assistance or the criteria for receiving such support.…”
Section: Study Inclusion Criteriamentioning
confidence: 99%
“…Task shifting, decentralization, and employment of lay health care workers have emerged as promising interventions to address this problem in low- and middle-income settings around the world, including India, Malawi, South Africa and Uganda. 15,41,4648 …”
Section: Introductionmentioning
confidence: 99%